Determinan Nilai Perusahan Perbankan Go public : Peran Green Banking, Profitabilitas, Kebijakan Dividen, dan Keputusan Investasi - Nurul Mustafida; Muhammad Arief Junivan Muhammad Arief Junivan (Prodi Akuntansi Syariah UIN Sulthan Thaha Saifuddin Jambi, 2025)
This research aims to analyze the influence of green banking, profitability, dividend policy, and investment decisions on the firm value of banking companies and those listed on the Indonesia Stock Exchange for 2019-2023. The quantitative methodology with a purposive sampling technique resulted in 64 research data analyzed using SPSS. The research results showed that Green Banking had a positive and significant effect on company value, profitability had a positive and significant effect on company value, Dividend policy did not show a significant effect, and investment decisions had a positive and significant effect on company value. Furthermore, this study provides insights into the importance of Green Banking and investment decisions in enhancing company value. It highlights the need for banking companies to prioritize sustainability and responsible investing practices.